A glass fiber modified polyester fiber composite material and preparation method thereof
By modified glass fiber and combined with other auxiliary agents, prepare polyester fiber composite materials with high fever stability, good flame retardant and insulation performance and excellent stretching strength and toughness, solve the polyester fiber composite material in terms of these performance Insufficient problem.
Patent Information
- Application Number
- CN202411430559.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Polyester fiber composites have shortcomings in thermal stability, flame retardant and thermal insulation properties and impact resistance, which affects their wide application.
By modified glass fiber, 3 (4-nitrolbhenyl) phosphate synthesizes phosphate containing vulnezolidone structures, combined with amino silline allex coupling agent, connected to the glass fiber, combined with other additives such as to achieve it Auctors, lubricants, and tough agents are prepared by melting the legal system.
It significantly improves the thermal stability of the composite materials, the flame retardant and thermal insulation performance, and the toughness and toughness of the stretching strength, which can better adapt to the high temperature conditions and show a better fire barrier effect during the combustion process.
Smart Images

Figure CN118956106B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyester fiber composite materials, and in particular relates to a glass fiber modified polyester fiber composite material and a preparation method thereof. Background Art
[0002] Polyester fiber is a synthetic fiber made of organic dibasic acid and diol by chemical polycondensation. It has many excellent properties, such as high strength, good wear resistance, chemical corrosion resistance and dimensional stability. It is widely used in many fields such as textiles, packaging, engineering materials, etc. Because its production process is relatively mature, the cost is low, and its performance can meet the needs of different industries in many aspects, it has become a very important synthetic material.
[0003] As a widely used synthetic fiber, polyester fiber has many excellent properties, but it still has limitations in some performance aspects, such as insufficient thermal stability, poor flame retardant and heat insulation performance, and poor impact resistance. In order to meet a wider range of application needs, fiber reinforcement modification technology has become one of the important means to improve the performance of polyester fiber composite materials. Fiber reinforcement modification is to form a multiphase system composite material by compounding high-strength and high-modulus fibers with polyester fibers. In this composite material, the reinforcing fiber, as the main component of the bearing stress, can effectively share the load and prevent the expansion of cracks when subjected to external forces, thereby improving the mechanical properties of the overall material. For example, glass fiber, carbon fiber, etc. have high specific strength and specific modulus. When combined with polyester fiber, they can greatly improve the strength and stiffness of the composite material. Glass fiber has the advantages of relatively low price and wide sources, high strength and good chemical stability, so it is often used in the blending modification of chemical fiber materials. However, the surface of glass fiber is relatively smooth and its chemical affinity with the polyester matrix is weak. Interface separation is prone to occur during the composite process, which affects the stress transfer efficiency and thus reduces the overall performance of the composite material. Therefore, it is necessary to find a new method for glass fiber to modify polyester fiber. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention uses polyester fiber as a matrix, modifies the polyester fiber by modified glass fiber, adds other additives, and obtains a composite material by melt extrusion. The composite material has high thermal stability, good flame retardant and heat insulating properties, and excellent tensile strength and toughness.
[0005] In order to achieve the above-mentioned object, the following technical scheme is adopted: In the first aspect, the present invention provides a glass fiber modified polyester fiber composite material, comprising the following components in parts by weight:
[0006] 50-70 parts of polyester fiber, 10-20 parts of modified glass fiber, 1-3 parts of nucleating agent, 0.5-2 parts of lubricant, and 3-5 parts of toughening agent.
[0007] The modified glass fiber is prepared by the following steps:
[0008] S1. Add tri(4-nitrophenyl)phosphate to 1 mol / L sodium hydroxide ethanol solution, control the temperature at 0°C to react for 30 min, then add 3 mol / L hydrochloric acid to adjust the pH to neutral, add potassium permanganate, and react at 20°C for 12 h. In this step,
[0009] The obtained solid is filtered, washed, and dried to obtain carbonyl phosphate;
[0010] S2, adding the carbonyl phosphate to DMSO, then adding nitromethane, potassium carbonate and sodium borohydride, reacting at 0°C for 2h, filtering, drying, then adding the obtained solid to deionized water, passing di-tert-butyl dicarbonate, reacting at 45°C for 2h, adding 3 mol / L sodium hydroxide solution to adjust the pH to 9, filtering, washing, and drying to obtain a phosphate containing an oxazolidinone structure;
[0011] S3, adding the phosphate containing the oxazolidinone structure to dichloromethane, adding phosphorus oxychloride, reacting for 1 hour, then adding 3 mol / L sodium hydroxide solution to adjust the pH to neutral, then adding N-methylmorpholine and aminosilane coupling agent, reacting for 12 hours, to obtain a modified coupling agent;
[0012] S4. Anhydrous ethanol and deionized water are mixed in a ratio of 2:3 to obtain an ethanol aqueous solution, the modified coupling agent is added, and after stirring for 1 hour, the glass fiber is immersed in the ethanol aqueous solution to obtain the modified glass fiber.
[0013] Furthermore, in step S1, the mass ratio of the sodium hydroxide ethanol solution, tri(4-nitrophenyl)phosphate and potassium permanganate is 100:3-7:1-6.
[0014] Furthermore, in step S2, the mass ratio of carbonyl phosphate, DMSO, nitromethane, potassium carbonate, sodium borohydride, deionized water and di-tert-butyl dicarbonate is 5:100-150:3-5:10-20:1-6:80-100:5-10.
[0015] Furthermore, in step S3, the mass ratio of the phosphate containing the oxazolidinone structure, dichloromethane, phosphorus oxychloride, N-methylmorpholine and aminosilane coupling agent is 10:200-300:1-5:0.1-0.5:4.5-6.
[0016] Furthermore, in step S4, the mass ratio of the ethanol aqueous solution to the modified coupling agent is 100:3-5.
[0017] Furthermore, the aminosilane coupling agent is selected from one of KH-550, KH-602, KH-792 and KH-902.
[0018] Furthermore, the nucleating agent is selected from one or more combinations of talc, mica powder, silicon dioxide, alum and titanium dioxide.
[0019] Furthermore, the lubricant is selected from one of polyoxyethylene stearate, polyethylene glycol stearate, propylene glycol stearate and pentaerythritol stearate.
[0020] Furthermore, the toughening agent is selected from one or more combinations of maleic anhydride grafted polypropylene, ethylene-butyl acrylate copolymer, polyolefin grafted glycidyl methacrylate, and ethylene-methyl acrylate-glycidyl methacrylate copolymer.
[0021] In a second aspect, the present invention also provides a method for preparing a glass fiber modified polyester fiber composite material, comprising the following steps: blending the components according to their respective weight portions, melt-extruding through a twin-screw extruder, cooling and drying, and obtaining the composite material.
[0022] The beneficial effects of the present invention are:
[0023] (1) The present invention reacts tri(4-nitrophenyl)phosphate to finally synthesize a phosphate containing an oxazolidinone structure, and then combines it with an aminosilane coupling agent and connects it to a glass fiber. The oxazolidinone structure has unique rigidity and stability, and can significantly hinder the free rotation of the molecular chain and the progress of the thermal decomposition reaction under high temperature environment, thereby reducing the energy transfer and thermal degradation between the molecular chains, thereby reducing heat conduction, playing a role in heat insulation, and greatly improving the thermal stability of the modified glass fiber and the entire composite material. After the glass fiber is modified, not only its own thermal stability is enhanced, but it can also better adapt to high temperature conditions during the preparation and use of the composite material;
[0024] (2) The modified glass fiber introduces nitrogen, phosphorus and silicon elements, which have a synergistic flame retardant effect. During the combustion process, phosphorus can form substances such as phosphoric acid or polyphosphoric acid. These substances will form a covering layer on the surface of the material, effectively isolating oxygen and preventing the further spread of combustion. Nitrogen decomposes at high temperature to produce non-combustible gas, diluting the concentration of combustible gas and oxygen, thereby playing a flame retardant role. Silicon promotes the formation of a dense carbon layer, enhancing the heat insulation and oxygen isolation properties of the material, and further preventing heat and flame from transferring to the interior of the material. The phosphorus-containing part of the oxazolidinone structure will undergo a chemical reaction during combustion to generate flame retardant phosphate substances. These substances quickly cover the surface of the material to form a fire barrier, preventing the transfer of heat and oxygen and slowing down the combustion rate. At the same time, the silicon element in the aminosilane coupling agent actively participates in the formation process of the carbon layer, making the carbon layer denser and more stable, further improving the flame retardant properties of the material.
[0025] (3) In the present invention, the phosphate containing oxazolidinone structure is coupled to the glass fiber through the action of the amino coupling agent, which significantly increases the interaction between the glass fiber and the polyester fiber chain segments. The amino group and the functional groups such as the carboxyl group in the polyester fiber may undergo hydrogen bonding or other chemical interactions, making the bonding between the glass fiber and the polyester fiber tighter. This synergistic effect enables the composite material to better withstand stress and is less likely to break, thereby improving the tensile strength and toughness of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a line graph of the thermal weight loss starting decomposition temperature of samples of different embodiments of the present invention and comparative examples;
[0027] Figure 2 It is a top view of the carbon residue of different embodiments and comparative examples of the present invention after the combustion test;
[0028] Figure 3 The thermal insulation performance test results of different embodiments and comparative examples of the present invention at different temperatures are shown in FIG.
[0029] Figure 4 The figures are the test results of mechanical properties of samples of different embodiments and comparative examples of the present invention.
[0030] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0033] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified. Example 1
[0034] A glass fiber modified polyester fiber composite material and preparation method thereof
[0035] The composite material comprises the following components in parts by weight:
[0036] 50 parts of polyester fiber, 10 parts of modified glass fiber, 1 part of nucleating agent, 0.5 parts of lubricant, and 3 parts of toughening agent.
[0037] The modified glass fiber is prepared by the following steps:
[0038] S1. Add tri(4-nitrophenyl)phosphate to 1 mol / L sodium hydroxide ethanol solution, control the temperature at 0°C to react for 30 min, then add 3 mol / L hydrochloric acid to adjust the pH to neutral, add potassium permanganate, react at 20°C for 12 h, filter the obtained solid, wash, and dry to obtain carbonyl phosphate;
[0039] S2, adding the carbonyl phosphate to DMSO, then adding nitromethane, potassium carbonate and sodium borohydride, reacting at 0°C for 2h, filtering, drying, then adding the obtained solid to deionized water, passing di-tert-butyl dicarbonate, reacting at 45°C for 2h, adding 3 mol / L sodium hydroxide solution to adjust the pH to 9, filtering, washing, and drying to obtain a phosphate containing an oxazolidinone structure;
[0040] S3, adding the phosphate containing the oxazolidinone structure to dichloromethane, adding phosphorus oxychloride, reacting for 1 hour, then adding 3 mol / L sodium hydroxide solution to adjust the pH to neutral, then adding N-methylmorpholine and aminosilane coupling agent, reacting for 12 hours, to obtain a modified coupling agent;
[0041] S4. Anhydrous ethanol and deionized water are mixed in a ratio of 2:3 to obtain an ethanol aqueous solution, the modified coupling agent is added, and after stirring for 1 hour, the glass fiber is immersed in the ethanol aqueous solution to obtain the modified glass fiber.
[0042] In the step S1, the mass ratio of sodium hydroxide ethanol solution, tris (4-nitrophenyl) phosphate and potassium permanganate is 100:3:1; in the step S2, the mass ratio of carbonyl phosphate, DMSO, nitromethane, potassium carbonate, sodium borohydride, deionized water and di-tert-butyl dicarbonate is 5:100:3:10:1:80:5; in the step S3, the mass ratio of phosphate containing oxazolidinone structure, dichloromethane, phosphorus oxychloride, N-methylmorpholine and aminosilane coupling agent is 10:200:1:0.1:4.5; in the step S4, the mass ratio of ethanol aqueous solution and modified coupling agent is 100:3; the aminosilane coupling agent is KH-550; the nucleating agent is talcum powder; the lubricant is stearic acid polyoxyethylene ester; and the toughening agent is maleic anhydride grafted polypropylene.
[0043] The preparation method of the composite material comprises the following steps: mixing the components according to their respective weight parts, melting and extruding through a twin-screw extruder, cooling and drying, and obtaining the composite material. Example 2
[0044] A glass fiber modified polyester fiber composite material and preparation method thereof
[0045] The composite material comprises the following components in parts by weight:
[0046] 70 parts of polyester fiber, 20 parts of modified glass fiber, 3 parts of nucleating agent, 2 parts of lubricant, and 5 parts of toughening agent.
[0047] In the step S1, the mass ratio of the sodium hydroxide ethanol solution, tris (4-nitrophenyl) phosphate and potassium permanganate is 100:7:6; in the step S2, the mass ratio of the carbonyl phosphate, DMSO, nitromethane, potassium carbonate, sodium borohydride, deionized water and di-tert-butyl dicarbonate is 5:150:5:20:6:100:10; in the step S3, the mass ratio of the phosphate containing the oxazolidinone structure, dichloromethane, phosphorus oxychloride, N-methylmorpholine and aminosilane coupling agent is 10:300:5:0.5:6; in the step S4, the mass ratio of the ethanol aqueous solution and the modified coupling agent is 100:5; the aminosilane coupling agent is KH791; the nucleating agent is silicon dioxide; the lubricant is polyethylene glycol stearate; and the toughening agent is ethylene-butyl acrylate copolymer.
[0048] The preparation processes of the modified glass fiber and the composite material are the same as those in Example 1. Example 3
[0049] A glass fiber modified polyester fiber composite material and preparation method thereof
[0050] The composite material comprises the following components in parts by weight:
[0051] 65 parts of polyester fiber, 15 parts of modified glass fiber, 1.8 parts of nucleating agent, 1.5 parts of lubricant, and 3.2 parts of toughening agent.
[0052] In the step S1, the mass ratio of sodium hydroxide ethanol solution, tris (4-nitrophenyl) phosphate and potassium permanganate is 100:6:4; in the step S2, the mass ratio of carbonyl phosphate, DMSO, nitromethane, potassium carbonate, sodium borohydride, deionized water and di-tert-butyl dicarbonate is 5:120:4:15:5:90:8; in the step S3, the mass ratio of phosphate containing oxazolidinone structure, dichloromethane, phosphorus oxychloride, N-methylmorpholine and aminosilane coupling agent is 10:250:2.5:0.25:5; In step S4, the mass ratio of the ethanol aqueous solution and the modified coupling agent is 100:4; the aminosilane coupling agent is KH-902; the nucleating agent is a combination of talc, silicon dioxide, alum and titanium dioxide in a mass ratio of 2:1:2:1.5; the lubricant is a combination of polyethylene glycol stearate, propylene glycol stearate and pentaerythritol stearate in a mass ratio of 0.8:1:2; the toughening agent is a combination of polyolefin grafted glycidyl methacrylate and ethylene-methyl acrylate-glycidyl methacrylate copolymer in a mass ratio of 3:2.
[0053] The preparation processes of the modified glass fiber and the composite material are the same as those in Example 1. Example 4
[0054] A glass fiber modified polyester fiber composite material and preparation method thereof
[0055] The composite material in this embodiment includes the following components in parts by weight:
[0056] 50 parts of polyester fiber, 20 parts of modified glass fiber, 1 part of nucleating agent, 0.5 parts of lubricant, and 3 parts of toughening agent.
[0057] The rest is the same as Example 3. Example 5
[0058] A glass fiber modified polyester fiber composite material and preparation method thereof
[0059] The composite material in this embodiment includes the following components in parts by weight:
[0060] 70 parts of polyester fiber, 10 parts of modified glass fiber, 1 part of nucleating agent, 0.5 parts of lubricant, and 3 parts of toughening agent.
[0061] The rest is the same as Example 4. Example 6
[0062] A glass fiber modified polyester fiber composite material and preparation method thereof
[0063] In this embodiment, the aminosilane coupling agent is KH-792, the nucleating agent is silicon dioxide, the toughening agent is pentaerythritol stearate, and the rest is the same as in Embodiment 4.
[0064] Comparative Example 1
[0065] In this comparative example, glass fiber is used instead of modified glass fiber to prepare the composite material, and the rest is the same as Example 4.
[0066] Comparative Example 2
[0067] In this comparative example, no oxazolidinone structure is introduced into the phosphate, that is, tri(4-nitrophenyl)phosphate is used to replace the phosphate containing the oxazolidinone structure in step S3, and the rest is the same as in Example 4.
[0068] Comparative Example 3
[0069] In this comparative example, the phosphate containing the oxazolidinone structure is not connected to the aminosilane coupling agent, and the rest is the same as Example 4.
[0070] The modified glass fiber is prepared by the following steps:
[0071] S1. Add tri(4-nitrophenyl)phosphate to 1 mol / L sodium hydroxide ethanol solution, control the temperature at 0°C to react for 30 min, then add 3 mol / L hydrochloric acid to adjust the pH to neutral, add potassium permanganate, react at 20°C for 12 h, filter the obtained solid, wash, and dry to obtain carbonyl phosphate;
[0072] S2, adding the carbonyl phosphate to DMSO, then adding nitromethane, potassium carbonate and sodium borohydride, reacting at 0°C for 2h, filtering, drying, then adding the obtained solid to deionized water, passing di-tert-butyl dicarbonate, reacting at 45°C for 2h, adding 3 mol / L sodium hydroxide solution to adjust the pH to 9, filtering, washing, and drying to obtain a phosphate containing an oxazolidinone structure;
[0073] S3, adding the phosphate containing the oxazolidinone structure into dichloromethane, then adding an aminosilane coupling agent, mixing anhydrous ethanol and deionized water in a ratio of 2:3 and adding the mixture into the dichloromethane solution, stirring for 1 hour and then immersing the glass fiber in the dichloromethane solution to obtain the modified glass fiber.
[0074] Test Example 1
[0075] Thermal stability test of composite materials
[0076] The TGA experiment was performed on the samples made of the composite materials of each embodiment and comparative example using a German TG209F3 Tarsus thermogravimetric analyzer. The conditions were: heating from room temperature 23°C to 800°C, heating rate 10°C / min, nitrogen purging, and then the starting thermal decomposition temperature was obtained by extrapolation according to the experimental curve. The higher the value, the stronger the material's ability to resist high temperature decomposition, that is, the higher the thermal stability. The thermal weight loss starting decomposition temperature of each embodiment and comparative example is as follows: Figure 1 .
[0077] Depend on Figure 1 It can be seen from the test results that the thermal weight loss starting decomposition temperature of the composite material prepared in the embodiment of the present invention is higher than that of the comparative example, because the present invention combines the phosphate containing the oxazolidinone structure with the aminosilane coupling agent and then connects it to the glass fiber. The oxazolidinone structure has unique rigidity and stability, which can hinder the free rotation and thermal decomposition reaction of the molecular chain under high temperature environment, reduce the energy transfer and thermal degradation between the molecular chains, thereby greatly improving the thermal stability of the modified glass fiber and the entire composite material. Since the glass fiber in the composite material in comparative example 1 is not modified, the oxazolidinone structure is not introduced into the phosphate in comparative example 2, and the phosphate is connected with the aminosilane coupling agent in comparative example 3, resulting in poor stability. Therefore, the thermal stability of Examples 1-3 is relatively weak, and the thermal weight loss starting decomposition temperature is low.
[0078] Test Example 2
[0079] Flame retardant properties test of composite materials
[0080] According to the standard of GB / T 8924-2005, the vertical combustion performance of the samples of each embodiment and comparative example was tested by using an AQC-694 UL94 combustion tester, and the sample size was 70 mm×7 mm×3 mm.
[0081] According to the standard of GB / T 2408-2008, the limiting oxygen index (LOI value) of each embodiment and comparative example sample was measured using a CSI-101D Chengsi fully automatic limiting oxygen index tester, and the sample size was 125 mm×13 mm×3 mm.
[0082] The results of the above two tests are shown in Table 1.
[0083] Table 1 Vertical combustion performance and limiting oxygen index test results
[0084] project UL Flame Retardant Rating LOI value / % Example 1 V0 38.8 Example 2 V0 41.0 Example 3 V0 42.2 Example 4 V0 41.5 Example 5 V0 39.5 Example 6 V0 40.5 Comparative Example 1 V2 18.0 Comparative Example 2 V1 22.5 Comparative Example 3 V1 24.5
[0085] The top view of the carbon residue after the combustion test of the samples of different embodiments and comparative examples is as follows Figure 2 .
[0086] It can be seen from the test results in Table 1 that nitrogen, phosphorus and silicon elements are introduced into the modified glass fiber, which has a synergistic flame retardant effect. At the same time, the phosphorus-containing part in the oxazolidinone structure generates flame retardant phosphate substances during combustion to form a fire barrier. The silicon element in the aminosilane coupling agent also actively participates in the formation of the carbon layer, making the carbon layer more dense and stable, and improving the flame retardant properties of the material. Therefore, Examples 1-6 perform better than Comparative Examples 1-3 in vertical combustion performance and limiting oxygen index tests, proving that the modified composite material has better flame retardant properties.
[0087] And through Figure 2 It can be seen that the carbon layer of Example 4 after combustion is relatively complete, while comparative examples 1-3 all show cracking to varying degrees, which further verifies that the modified composite material of the present invention has more excellent flame retardant properties. In Example 4, since the glass fiber is modified to introduce nitrogen, phosphorus, silicon elements and phosphate containing an oxazolidinone structure, these elements work synergistically during the combustion process to form a denser and more stable carbon layer. The modified glass fiber is more tightly combined with the polyester fiber, which can better maintain the structural integrity of the material during the combustion process, thereby improving the high temperature resistance of the composite material.
[0088] Test Example 3
[0089] Thermal insulation performance test
[0090] The thermal conductivity of the samples of Example 4 and Comparative Examples 1-3 at different temperatures was measured by transient plane heat source method using a DRE-2C thermal conductivity tester. The sample thickness was 10 mm. The test results are shown in FIG. Figure 3 .
[0091] Depend on Figure 3 It can be seen from the test results that the sample of Example 4 has lower thermal conductivity at 20, 25, 30, 35 and 40°C, and the change in thermal conductivity with temperature is small, so the thermal insulation performance is better than that of Comparative Examples 1-3. This is because the oxazolidinone structure can significantly hinder the free rotation of the molecular chain and the thermal decomposition reaction in a high temperature environment, reducing the energy transfer and thermal degradation between the molecular chains, thereby reducing heat conduction and playing a role in heat insulation. The composite material in the comparative example has relatively weak thermal insulation performance because the glass fiber has not been modified in the present invention.
[0092] Test Example 4
[0093] Composite material mechanical properties testing
[0094] The tensile strength of the samples of each embodiment and comparative example was tested according to the standard of ASTM D3039 using a CEAST 5982 universal material testing machine, with a sample size of 10 mm × 10 mm × 150 mm, a tensile speed of 500 mm / min, and a clamping distance of 40 mm. The impact strength of the samples of each embodiment and comparative example was tested according to the standard of ISO 180 using a CEAST 9350 drop hammer impact testing machine. The test results are shown in FIG. Figure 4 .
[0095] Depend on Figure 3 It can be seen from the test results that the phosphate ester containing an oxazolidinone structure is coupled to the glass fiber through the action of the amino coupling agent, which significantly increases the interaction between the glass fiber and the polyester fiber segment, making the glass fiber and the polyester fiber more tightly bonded. The amino group and the functional groups such as the carboxyl group in the polyester fiber may undergo hydrogen bonding or other chemical interactions. This synergistic effect enables the composite material to better withstand stress and is less likely to break, thereby improving the tensile strength and toughness of the composite material.
[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0097] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A glass fiber modified polyester fiber composite material, characterized in that: The composition comprises the following components in parts by weight: 50-70 parts of polyester fiber, 10-20 parts of modified glass fiber, 1-3 parts of nucleating agent, 0.5-2 parts of lubricant, 3-5 parts of toughening agent; The modified glass fiber is prepared by the following steps: S1. Add tri(4-nitrophenyl)phosphate to 1 mol / L sodium hydroxide ethanol solution, control the temperature at 0°C to react for 30 min, then add 3 mol / L hydrochloric acid to adjust the pH to neutral, add potassium permanganate, react at 20°C for 12 h, filter the obtained solid, wash, and dry to obtain carbonyl phosphate; S2, adding the carbonyl phosphate to DMSO, then adding nitromethane, potassium carbonate and sodium borohydride, reacting at 0°C for 2h, filtering, drying, then adding the obtained solid to deionized water, passing di-tert-butyl dicarbonate, reacting at 45°C for 2h, adding 3 mol / L sodium hydroxide solution to adjust the pH to 9, filtering, washing, and drying to obtain a phosphate containing an oxazolidinone structure; S3, adding the phosphate containing the oxazolidinone structure to dichloromethane, adding phosphorus oxychloride, reacting for 1 hour, then adding 3 mol / L sodium hydroxide solution to adjust the pH to neutral, then adding N-methylmorpholine and aminosilane coupling agent, reacting for 12 hours, to obtain a modified coupling agent; S4. Anhydrous ethanol and deionized water are mixed in a ratio of 2:3 to obtain an ethanol aqueous solution, the modified coupling agent is added, and after stirring for 1 hour, the glass fiber is immersed in the ethanol aqueous solution to obtain the modified glass fiber.
2. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: In the step S1, the mass ratio of the sodium hydroxide ethanol solution, tri(4-nitrophenyl)phosphate and potassium permanganate is 100:3-7:1-6.
3. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: In the step S2, the mass ratio of carbonyl phosphate, DMSO, nitromethane, potassium carbonate, sodium borohydride, deionized water and di-tert-butyl dicarbonate is 5:100-150:3-5:10-20:1-6:80-100:5-10.
4. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: In the step S3, the mass ratio of the phosphate containing the oxazolidinone structure, dichloromethane, phosphorus oxychloride, N-methylmorpholine and aminosilane coupling agent is 10:200-300:1-5:0.1-0.5:4.5-6.
5. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: In step S4, the feed mass ratio of the ethanol aqueous solution to the modified coupling agent is 100:3-5.
6. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: The aminosilane coupling agent is selected from one of KH-550, KH791, KH-792 and KH-902.
7. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: The nucleating agent is selected from one or more combinations of talc, mica powder, silicon dioxide, alum and titanium dioxide.
8. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: The lubricant is selected from one of polyoxyethylene stearate, polyethylene glycol stearate, propylene glycol stearate and pentaerythritol stearate.
9. The glass fiber modified polyester fiber composite material according to claim 1, characterized in that: The toughening agent is selected from one or more combinations of maleic anhydride grafted polypropylene, ethylene-butyl acrylate copolymer, polyolefin grafted glycidyl methacrylate, and ethylene-methyl acrylate-glycidyl methacrylate copolymer.
10. A method for preparing the glass fiber modified polyester fiber composite material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing the components according to their respective weight parts, melting and extruding the components through a twin-screw extruder, cooling and drying the components to obtain the composite material.
Citation Information
Patent Citations
Composite material for reinforcing plate and preparation method thereof
CN118085560A
Resin reinforcing fiberglass and thermoplastic resin composition
US20200247962A1